Agrobiodiversidade e soberania alimentar na Floresta Nacional do Rio Purus, Amazônia: contribuições do Santo Daime e de práticas agroecológicas - Paula, Juliana Carla Silva (Universidade Federal de São Carlos, 2024)
For millennia, Amazonian people have managed forest resources. This relationship between culture and nature is important for the maintenance of Amazonian agroecosystems. The landscapes of this region are characterized by diversity and long coexistence with human beings. In the Amazon today, people live with total or partial dependence on forest resources for their well-being and with in-depth local knowledge. Among the variety of cultural practices that exist within the forest, Santo Daime emerges, a religious movement that emerged in the Amazon in 1930, resulting from the experience of Raimundo Irineu Serra, a migrant from Maranhão who works in the rubber cycle in the State of Acre. The objective of this research is to investigate how religious identity influences the lifestyle of these people, having similarities with the principle of Agroecology and a high maintenance of Agrobiodiversity that results in the strengthening of Food Sovereignty. We used oral history, participant observation and MESMIS (Marco para la Evaluación de Sistemas de Manejo de Recursos Naturales) as methodology, incorporating Sustainability Indicators). The study area was in the Purus River National Forest (FLONA Purus) and region, located in the State of Amazonas, municipality of Pauini, in four different communities. All of them culturally linked by the religion of Santo Daime, a religion that uses the drink ayahuasca during its rituals, which is prepared from two Amazonian plants. The results are presented through four main axes, namely: 1) the interconnection between the Santo Daime culture and its link with agroecology; 2) the survey of Agrobiodiversity in practice, 3) the trajectory followed by Cooperar; the Agroecology and Food Sovereignty nucleus of Mapiá and middle Purus; and 4) the analysis of sustainability indicators. We observed the familiarity between the practices of Santo Daime followers and agroecological principles, we inferred a high maintenance of Agrobiodiversity, supporting the maintenance of Food Sovereignty. With a survey of 118 agrobiodiversity spec ies, for food, nutritional or medicinal purposes. The results obtained through sustainability indicators reveal a mixed situation regarding the sustainability of the agroecosystems studied. With regard to environmental indicators, it is observed that a significant part of the parameters are classified as good, in the economic sphere, the results less than 50% are good, with regard to social indicators, the results indicate important challenges, with less 50% of the parameters being good and 33% being a bad parameter. In this way, we can conclude that religious identity is driving a motivation to seek food sovereignty and maintains a high level of agrobiodiversity, however, according to sustainability indicators, challenges will have to be achieved to remain this way.
Agrobiodiversity and food sovereignty in the Purus River National Forest, Amazon: contributions from Santo Daime and agroecological practices
Keywords: Agrobiodiversidade; Soberania Alimentar; Indicadores de sustentabilidade; Santo Daime; Agrobiodiversity; Food sovereignty; Sustainability indicators; CIENCIAS AGRARIAS::AGRONOMIA::EXTENSAO RURAL; CIENCIAS AGRARIAS::AGRONOMIA::FLORICULTURA, PARQUES E JARDINS; CIENCIAS HUMANAS::ANTROPOLOGIA::ANTROPOLOGIA RURAL; CIENCIAS HUMANAS::HISTORIA